THE USE OF SENTENCE OUTLINE TO IMPROVE STUDENTS’ WRITING ABILITY - Nur Qalby; Adil Ivery (Universitas Muhammadiyah Makassar, 2013)
The research questions of this research were how does sentence outline improve the students of the second year of SMP Negeri 4 Sungguminasa ability to write the paragraph? The researcher used A Classroom Action Research (CAR). The aims of this research are to find out the improvement of students’ writing skill and their activeness in the learning process through Writing Process Approach. Two cycles had been conducted, where each cycle consisted of four meetings. It employed writing test as the instrument. A number of subjects of the research were 42 students in the second grade conducted of 31 women and 11 men. The researcher took real data from the school to know the students’ writing ability. The results of the student's writing test in cycle 1 and cycle 2 had increased in different scores. There was increasing by students at the end action of the second cycle. The research findings indicated that use of writing process approach could increase the students’ writing skill. The means scores of students in the Diagnostic test was 59.84 became 66.64 in cycle 1, and after revision, in the cycle 2, the mean score in cycle 2 was 70.79 by implemented of sentence outline. The successful of minimal criteria (KKM) was 65 while cycle 1, there were 2 (4.76%) students get poor, 27 (64.29%) get fair, and 13 (30.95%) get good meant that students who achieved the successful minimal criteria (KKM) more than a half of them. In cycle 2 there was 25 (59.52%) get fair and 17 (40.48%) get fair.Keyword: Sentence, outline, improve, ability.